Performance in sampled data systems - Whidborne, James F. (IEEE, 1992)
A performance index for control systems has been defined as the supremum of the absolute error that occurs over all time and all inputs. The input to the system is known only to the extent that it belongs to a known function space. The paper shows how this performance index is determined for certain sampled data systems with an input space characterised only by a bound on the derivative of the input. An example of a design using this performance index is given.